Matérialiser la frontière autour de l’empereur dans l’Antiquité tardive - Maxime Emion (Frontière·s)
This paper investigates the various elements materialising a frontier between the emperor and common mortals in Late Antiquity, between the 4th and the 6th century AD, especially in the framework of the imperial court ceremonial. The reinforced importance of the palatial space established a dichotomy between inside and outside, and multiplied the thresholds separating the emperor and his subjects. The ever-present bodyguards were also a tangible yet mobile limit around the emperor, ensuring his security and contributing to his majesty. The imperial purple was the ultimate barrier around the ruler’s body and acted as a medium to approach the sacred nature of his power during the ceremony of adoratio. The interplay of material realities, rhetoric of sacredness, and ritual practices blurred the limits between image and reality, and turned the emperor himself into a frontier-being, belonging to both the earthly and the heavenly worlds.